Pengembangan Kecerdasan Intrapersonal Melalui Permainan Face Poly - Simanjuntak, Ade Veni Yunianti; Eva Indrianti; Yasmine Nabila; Harianja, Sri Indriani; Muazzomi, Nyimas (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2024)
Face Poly is a tool for developing intrapersonal intelligence. Face Poly, a method involving the analysis of facial expressions, is hypothesized to provide insight into an individual's emotions and feelings. This study explores how Face Poly can be used to improve self-awareness, emotional regulation, and internal motivation, which are important components of intrapersonal intelligence. This study will use a qualitative approach by involving early childhood participants who will play the Face Poly game and then be asked to reflect on their experiences. The results of the study can be concluded that the Face Poly game can be an effective way to encourage the development of intrapersonal intelligence in early childhood. This game also helps them in developing important social and emotional skills in their lives.